Tecnologias no ensino e aprendizagem da álgebra: análise das dissertações produzidas no Programa de Estudos de Pós-graduados em Educação Matemática da PUC-SP de 1994 até 2007 - Pinto, Gláucia (2009)
Inspired by KATZ (2007), this dissertation analyses 17 (seventeen) dissertations from the Post- Graduated Studies in Mathematical Education Program of Pontifícia Universidade Católica de São Paulo (PUC-SP) which were published since 1994 through the year of 2007. For those dissertations selection we took as theoretical framework the concepts from ROMBERG's (1992) state of the art and then from the abstracts, keywords and titles we filter this institution's academic and professional master in sciences dissertations for we select the researches that involved the algebric teaching and used technologies for impulsing it. This analysis goal was to verify which advantages and disadvantages the use of new technologies (computer, calculator and robotic gadgets) brings for the Algebra s teaching and learning under the perspective of dissertations from the PUC-SP s Post- Graduated Studies in Mathematical Education Program from 1994 to 2007. Thus, this work brings a consideration about the selected dissertations regarding how theirs strategies influenced the results pointed in the works and categorizing them in respect to their behavior according to the Algebra's dimension used, following the National Curricular Parameters (PCN, 1998). In the end, we conclude that the contents from eight dissertations which used technology for impulsing the algebric learning, while the other nine analysed dissertations contents brought only the advantages that the technology use brought to the aprentice